Development of a model for predicting the reliability indicators in the design of cascade thermoelectric coolers - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
Here we report a development of the reliability-oriented model, which makes it possible to evaluate the efficiency of functioning and to predict indicators of reliability of a two-cascade thermoelectric cooler. The model is proposed for the interrelation between indicators of reliability of two-cascade thermoelectric coolers at sequential electrical connection of cascades and basic parameters under the mode of maximum refrigeration coefficient. The relations onbtained allow us to estimate both the basic parameters and the indicators of reliability, in particular: the failure rate and the probability of failure-free operation of the chosen variant of design of a two-cascade thermoelectric cooler at the specified ratio of the number of thermoelements in the cascades and the assigned temperature differential. It is demonstrated that by manipulating the operating current and the ratio of the number of thermoelements in the cascades of a cooler in the range of functioning temperatures, it is possible to determine the conditions, which correspond to the maximum of refrigeration coefficient. We obtained an analytical dependence of the relation between relative failure rate and the number of thermoelements in the cascades, thermal load, operating currents and the values of temperatures. We examined the model for a fixed geometry of thermoelements, working range of temperature differential at the variation in the relation of the number of thermoelements in the cascades of a thermoelectric cooler. An analysis of the calculated data revealed that there is an optimum relation of the number of elements in the cascades, which corresponds to the maximum of refrigeration coefficient at the assigned temperature differential. In the point of the maximum of refrigeration coefficient there is the equality between values of relative drop in temperature and the refrigeration coefficients in cascades. The given data make it possible to estimate the efficiency of functioning and to predict reliability indicators of a two-cascade TED of the chosen design under the mode Emax under different operating conditions.